Prevalence of smoking and smoking cessation and associated factors in diabetes population aged 50 years and over in Europe - Malinovská, Jana; Lustigová, Michala; Michalec, Juraj; Krollová, Pavlína; Fruhaufova, Anna; Bučková, Lucia; Romanová, Alexandra; Beňová, Kristýna; Povolná, Ema; Guru, Emmanuel Stephen; Kozmíková, Kamila; Brož, Jan (Scientific reports, 2025)
The aim of this study was to determine prevalence of smokers and ex-smokers in the older diabetes population in Europe and to evaluate the relationship with various sociodemographic and lifestyle risk factors. This epidemiological study used Wave 8 of the multidisciplinary and cross-national SHARE database, which includes cross-sectional data on health, socio-economic status and social and family networks of individuals aged 50 and over from 27 European countries. Among the 6,903 participants with diabetes, 12.2% were current smokers, 29.9% were former smokers and 57.9% had never smoked. Among countries' diabetes populations, the highest prevalence of ex-smokers (57.6%) with a low prevalence of smokers (9.5%) was seen in the Netherlands. The highest prevalence of never-smokers (84.2%) was found in Latvia, with the lowest prevalence of ex-smokers (7.9%). Austria had the highest prevalence of current smokers (17.9%) along with a below-average prevalence of ex-smokers (26.5%) was seen in Austria. Normal weight, being overweight, lower education, living without a partner, living in larger cities, drinking alcohol in the last 7 days, lower age, and being male were associated with a higher risk of being a current smoker. The study shows high prevalence of smoking among the older diabetes population in Europe and provides data on the association of smoking with several risk factors and country-specific differences in smoking prevalence.
Keywords: SHARE; Humans; lidé středního věku; prevalence; Female; rizikové faktory; Aged; senioři; lidé; Smoking cessation; Europe; European population; odvykání kouření; Diabetes Mellitus; Diabetes; Smoking Cessation; ženské pohlaví; Life Style; Male; životní styl; Middle Aged; Risk factors; Aged, 80 and over; Cross-Sectional Studies; Prevalence; senioři nad 80 let; Smoking; mužské pohlaví; kouření; diabetes mellitus; průřezové studie; Evropa; Risk Factors